Effectiveness of gait analysis in management of osteoarthritis knee at primary care settings in Asia: a systematic review and meta-analysis protocol - Rastogi, Aavrati; Kalia, Roop B.; Yadav, Rajkumar; Neyaz, Osama (International Journal of Research in Orthopaedics, 2024)
Background: This systematic review will focus on the effectiveness of gait analysis on osteoarthritis knee management. The objectives of this systematic review and meta-analysis are to synthesize the clinical effectiveness and to compare the effectiveness of gait analysis in the osteoarthritis knee management in Asian population. Methods: This review will be conducted and reported according to PRISMA guidelines. To discover relevant papers, the search technique will use MeSH terms such as osteoarthritis knee, gait analysis, osteoarthritis knee management, primary healthcare, effectiveness, and Asia. Other synonymous words will be searched using the Boolean operator "and"/"or" on PubMed, Embase, Scopus, and Cochrane. Randomized controlled trials assessing the efficacy of gait analysis in the therapy of osteoarthritis knee patients in primary care settings in Asia will be considered. A random effects meta-analysis will be carried out using the REVMAN software version 5.3.5. The STATA software version SE16 will be used for both cumulative and comparative meta-analysis. Conclusions: This review and meta-analysis will be among the first to give an extensive purview on the effectiveness of gait analysis in osteoarthritis knee management at primary care settings in Asian population. This study will also acknowledge the effects of different gait analysis strategies with an attempt to compare the same. Trial Registration: The protocol has been registered at the International Prospective Register of Systematic Reviews (PROSPERO registration number: CRD42024540444).